(untitled) (Annals of Medical Research, 2024)
Aim: Insulin resistance is one of the most common causes of liver fibrosis. Instead of the Homeostatic Model Assessment- Insulin Resistance (HOMA-IR) index, which has been used to indicate insulin resistance for many years, Triglyceride-Glucose index (TyG) has recently been used, which is thought to be more predictive. (AST) to Platelet Ratio Index (APRI) and Fibrosis-4 Index (FIB-4) are newly developed markers to indicate liver fibrosis. In this study, we aimed to examine the relationship between TyG and HOMA-IR and APRI and FIB-4. Materials and Methods: 8,618 patients who applied to Turgut Özal Medical Center internal medicine outpatient clinic between March 2019 and March 2024 were retrospectively examined. APRI and FIB-4 levels were compared in patients by grouping them by age and as having/not having insulin resistance according to TyG and HOMA-IR Results: There was a statistically significant positive correlation between TyG with APRI and FIB4. (ρ= 0.041, p<0.001 for APRI and ρ= 0.109, p<0.001 for FIB4). There was a significant difference in APRI and FIB-4 in the grouping made according to the presence of insulin resistance. In the grouping made according to glycemic status, FIB-4 was significantly different among all subgroups ( p<0.001 for each), while there was no significant difference in APRI. Conclusion: Insulin resistance is one of the conditions that should be closely monitored not only because it predisposes to diabetes but also because it causes dysfunction in liver. Newly diagnosed indexes may be useful to follow-up these patients before any symptoms ocur. Widespread use of these indices especially FIB-4 index which we claim that it is more predictive than others, in clinical practice may be beneficial due to their predictive effects and noninvasiveness.